Health-related behaviors and symptoms of anxiety and depression in Spanish nursing students: an observational study - Ramón-Arbués, Enrique; Sagarra-Romero, Lucía; Echániz-Serrano, Emmanuel; Granada-López, José Manuel; Cobos-Rincón, Ana; Juárez-Vela, Raúl; Navas-Echazarreta, Noelia; Antón-Solanas, Isabel (Frontiers in Public Health, 2023)
Background: Symptoms of anxiety and depression are prevalent among young adults and are a significant public health issue. College students are at a higher risk of experiencing poor mental health than other young people due to several factors, including moving away from home, financial pressures, heavy workload, poor time management skills, competitivity, new processes of socialization and insufficient coping mechanisms, among others. In addition, nursing students' mental and physical health may also be affected by unhealthy lifestyle habits and health-related behaviors.Aim: To determine the prevalence of symptoms of depression and anxiety, and the association between these symptoms and health-related behaviors, in a population of Spanish student nurses.Methods: Cross-sectional study on a sample of 339 nursing students. We used the Hospital Anxiety and Depression Scale, the International Physical Activity Questionnaire-Short form, the Spanish Healthy Eating Index and an "ad hoc" questionnaire for sociodemographic variables. The association between psychological symptoms and health-related behaviors was analyzed through binary logistic regression models.Results: The prevalence of symptoms of depression and anxiety was 3.8% and 24.5%, respectively. Negative health-related behaviors were frequent, namely tobacco and alcohol consumption, suboptimal physical activity and diet. Moderate physical activity was associated with a lower probability of experiencing depressive symptoms.Symptoms of anxiety were related to a low level of physical activity, an unhealthy diet and alcohol consumption ≥2 times a week. Conclusion: Student nurses could benefit from the implementation of both physical and mental health promotion initiatives.